The security risks created by cloud migration and how to overcome them. Issue 4 (April 2020) - Kelf, Simon
Abstract : More than half of UK businesses are expected to migrate to the cloud by the end of the year, but concerns over security remain among some contemplating the move. While there are tremendous upsides to using the cloud over traditional data storage methods, there are some risks that arise during the migration process.